The stress concentration in an elastoplastic spherical shell with a number of identical circular holes - Chernyshenko, I.S.; Rudenko, I.B.; Storozhuk, E.A. (Reports of the National Academy of Sciences of Ukraine, 2017)
The statement of periodic static problems for an elastoplastic spherical shell with a number of identical circular holes is given. A technique for the numerical solution of a given class of nonlinear problems is developed, based on the use of the method of additional stresses and the variational vector-difference method. The effect of plastic deformations and geometric parameters on the stress-strain state of a spherical shell with a number of holes under the action of a uniform internal pressure is investigated.